2018
DOI: 10.3233/adr-180080
|View full text |Cite
|
Sign up to set email alerts
|

Are Porphyromonas gingivalis Outer Membrane Vesicles Microbullets for Sporadic Alzheimer’s Disease Manifestation?

Abstract: Our research into Alzheimer's disease (AD) focuses on the oral cavity and the brain, from which key evaluations of prospective and retrospective population-based data have shown that chronic periodontal disease existing for ten-years or over doubles the risk for the sporadic form of AD. Furthermore, Porphyromonas gingivalis (P. gingivalis) mono-infections in established periodontal lesions, or introducing its lipopolysachharide (LPS), as demonstrated in in vivo studies, show hallmark pathology inclusive of ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 84 publications
0
41
0
1
Order By: Relevance
“…P. gingivalis LPS promotes M1 macrophage polarization. But current researches indicate that gingipains, pili, and capsule all involve in chronic PD [ 31 , 39 ]. P. gingivalis as anaerobic bacteria lives in the gingival crevicular fluid that directly contacts oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…P. gingivalis LPS promotes M1 macrophage polarization. But current researches indicate that gingipains, pili, and capsule all involve in chronic PD [ 31 , 39 ]. P. gingivalis as anaerobic bacteria lives in the gingival crevicular fluid that directly contacts oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Outer membrane vesicles (OMVs) are secreted by bacteria, range from 20 to 250 nm in diameter, and carry bacterial lipopolysaccharide (LPS), protease, membrane receptor, DNA, RNA and so forth (Bonnington & Kuehn, 2014;Guerrero-Mandujano, Hernandez-Cortez, Ibarra, & Castro-Escarpulli, 2017;Jan, 2017). Several studies suggested that OMVs play a vital role in the communication and regulation of the host (Maerz et al, 2018;Rosenthal et al, 2014;Sinha et al, 2015) and even indicated that OMVs are related to AD (Aguayo, Schuh, Vicente, & Aguayo, 2018;Olsen, Taubman, & Singhrao, 2016;Singhrao & Olsen, 2018).…”
mentioning
confidence: 99%
“…P. gingivalis -LPS is released after the lysis of bacteria or as free vesicles outward from the outer membranes of living bacteria. These LPS-containing microvesicles, which function like “microbullets” that land on the host, further perpetuate the invasiveness of P. gingivalis , giving it the ability to destroy periodontal tissues and trigger inflammation (Zhang et al, 2015; Singhrao and Olsen, 2018). The basic chemical composition of P. gingivalis -LPS is nearly identical to that of a typical bacterial endotoxin.…”
Section: Effect Of Lps On P Gingivalis Virulencementioning
confidence: 99%